2012
DOI: 10.1093/cid/cis1000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-1 Subtype on CD4 Count at HIV Seroconversion, Rate of Decline, and Viral Load Set Point in European Seroconverter Cohorts

Abstract: HIV-1 subtype significantly influences seroconversion CD4 cell levels and decline rates but not viral load set point. These findings may be helpful to HIV-positive individuals and their attending physicians in understanding disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 29 publications
8
69
0
Order By: Relevance
“…However, as the Department of STD, AIDS and Viral Hepatitis routinely links SISCEL to the National System of Notified HIV/AIDS cases [34], it is possible to obtain exposure category for at least 70% of the SISCEL cases, enabling the estimation of HIV incidence by exposure category with the use of imputation methods [35]. Moreover, any other information available in SISCEL related to the time since infection, such as viral load or patient's condition (symptomatic/asymptomatic) that could be used to refine our estimates [36,37] will be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the Department of STD, AIDS and Viral Hepatitis routinely links SISCEL to the National System of Notified HIV/AIDS cases [34], it is possible to obtain exposure category for at least 70% of the SISCEL cases, enabling the estimation of HIV incidence by exposure category with the use of imputation methods [35]. Moreover, any other information available in SISCEL related to the time since infection, such as viral load or patient's condition (symptomatic/asymptomatic) that could be used to refine our estimates [36,37] will be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical studies have addressed the differences in disease progression between viral subtypes and outcomes. Toulomi et al 17 revealed that CD4 + T lymphocyte decline was significantly slower for subtype A and CRF02 and marginally slower for subtype C compared to subtype B. In addition, a previous study reported that subtype D is associated with faster disease progression, rapid CD4 + T cell decline, and a higher rate of treatment failure compared to subtypes A, B, and C 18 .…”
Section: Discussionmentioning
confidence: 97%
“…Starting from a uniform prior distribution for the seroconversion date over time at risk, we incorporated information from available CD4 cells counts and HIV-RNA levels measurements before AIDS development and ART initiation. CD4 cell counts and HIV-RNA trajectories from HIV seroconversion were estimated by a bivariate linear mixed model (LMM) fitted to natural history data from the CASCADE collaboration [20]. CASCADE comprises data of over 30.000 HIV-positive persons with documented dates of HIV seroconversion from 29 cohorts across Europe, Canada and Australia.…”
Section: Statistical Analysesmentioning
confidence: 99%